"You Have Mistaken Assumptions": How Parents' Role, Parents' Prep-for-Bias, and Children's Ethnic Self-Label are Interrelated Among Transracial Adoptions from China - Hobert, Olivia. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Child Development.; Advisor: Ellen Pinderhughes.; Committee: M Ann Easterbrooks, and Xian Zhang.; Keywords: Psychology, Developmental psychology, and Asian American studies.